Proyecto de factibilidad para la creación de una empresa importadora y comercializadora de “Equipos de hemodiálisis en el hogar” para la ciudad de Loja - Veintimilla Sánchez, Andrés Oswaldo (2015)
This thesis aims to determine the feasibility for the creation of an importer and marketer of "Equipment Hemodialysis at Home" for the City of Loja company; which it is intended to help people who use these devices have a better lifestyle. For this focused objectives for market research, a technical study, an analysis of the internal administrative structure and financial study to finally realize the economic evaluation through the application of financial indicators they unveiled the project's profitability . In the process the inductive, deductive and analytical methods used and the techniques of direct observation and survey, the sample size was determined considering the population of the health institutions in the city of Quito, with these results, the survey of 48 799 families in the city of Loja, with the application of 396 surveys were applied. In the course of the investigation, first market study was conducted, and demonstrates that there is an unmet demand for equipment to cover 2,692 Lojano in the market and all this for the first year of life of the project; so the company would have to cover a large market in the city of Loja. Within the technical study it determined that the company installed capacity of 823 hemodialysis equipment and installed capacity used and is measured in percent of installed capacity above 90% because in normal conditions, will not meet outstanding orders and if makes can be significantly altered the structure of costs, so this new company will initially work with 70%, and it will increase capacity utilization 5% annually to reach 90%. In the administrative study we determined the constitution of the company, which will have the same legal name of the company, will be "HEALTHY LIVING CIA. LTDA ". the same as contained in structural and functional and positional organization, also developing the manual functions. The financial study established that the initial investment will be $ 345,308.51, to be financed with the support of shareholders and credit, also in the economic evaluation a NPV of $ 5'583.175,19 was obtained, it was also determined an IRR of 242.65%, plus the investment is recovered in 1 year, 6 months and 18 days, defined likewise, a profit-Short ratio of 1.30 and finally specified that the project will support up to an increase of 24.66% costs and a decrease of up to 18.86% of revenue; so all the results of the economic evaluation are positive and favorable